Coronary Bypass Surgery in a 105-Year-Old Patient with Cardiopulmonary Bypass - Temucin Noyan Ogus; Filiz Erdim; Ozer Selimoglu; Fatih Tekiner; Murat Ugurlucan (Case Reports in Medicine)
Coronary artery bypass grafting is one of the routine daily surgical procedures in the current era. Parallel to the increasing life expectancy, cardiac surgery is commonly performed in octogenarians. However, literature consists of only seldom reports of coronary artery bypass grafting in patients above 90 years of age. In this report, we present our management strategy in a 105-year-old patient who underwent coronary artery bypass grafting at our institution.